2020
DOI: 10.3389/fcell.2020.00577
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA339 Targeting PDXK Improves Motor Dysfunction and Promotes Neurite Growth in the Remote Cortex Subjected to Spinal Cord Transection

Abstract: Spinal cord injury (SCI) is a fatal disease that can cause severe disability. Cortical reorganization subserved the recovery of spontaneous function after SCI, although the potential molecular mechanism in this remote control is largely unknown. Therefore, using proteomics analysis, RNA interference/overexpression, and CRISPR/Cas9 in vivo and in vitro, we analyzed how the molecular network functions in neurological improvement, especially in the recovery of motor function after spinal cord transection (SCT) vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 63 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…The four-min evaluation on each rat was made and scores of hindlimb movement were recorded by three experienced researchers. The average score was the final score [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…The four-min evaluation on each rat was made and scores of hindlimb movement were recorded by three experienced researchers. The average score was the final score [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the same study, knockout of the microRNA (MiR339) that blocks PDXK translation was shown to decrease apoptosis of cortical neurons, thereby increasing neurite outgrowth [72].…”
Section: The Shared Genetic Origin Of the Vitamin-related Forms Of Cm...mentioning
confidence: 88%